Omega 3 polyunsaturated fatty acid improves spatial learning and hippocampal Peroxisome Proliferator Activated Receptors (PPARα and PPARγ) gene expression in rats - Hajjar, Toktam; Goh, Yong Meng; Rajion, Mohamed Ali; Vidyadaran, Sharmili; Othman, Fauziah; Farjam, Abdoreza Soleimani; Tan, Ai Li; Ebrahimi, Mahdi (BioMed Central, 2012)
Background: This study examined the effects of dietary polyunsaturated fatty acids (PUFA) as different n-6: n-3 ratios on spatial learning and gene expression of peroxisome- proliferator-activated receptors (PPARs) in the hippocampus of rats. Thirty male Sprague–Dawley rats were randomly allotted into 3 groups of ten animals each and received experimental diets with different n-6: n-3 PUFA ratios of either 65:1, 22:1 or 4.5:1. After 10 weeks, the spatial memory of the animals was assessed using the Morris Water Maze test. The expression of PPARα and PPARγ genes were determined using real-time PCR. Results: Decreasing dietary n-6: n-3 PUFA ratios improved the cognitive performance of animals in the Morris water maze test along with the upregulation of PPARα and PPARγ gene expression. The animals with the lowest dietary n-6: n-3 PUFA ratio presented the highest spatial learning improvement and PPAR gene expression. Conclusion: It can be concluded that modulation of n-6: n-3 PUFA ratios in the diet may lead to increased hippocampal PPAR gene expression and consequently improved spatial learning and memory in rats.